Glacier Algae: A Dark Past and a Darker Future - Williamson, Christopher J.; Cameron, Karen A.; Cook, Joseph M.; Zarsky, Jakub D.; Stibal, Marek; Edwards, Arwyn (Frontiers in Microbiology, 2019)
‘Glacier algae’ grow on melting glacier and ice sheet surfaces across the cryosphere, causing the ice to absorb more solar energy and consequently melt faster, while also turning over carbon and nutrients. This makes glacier algal assemblages, which are typically dominated by just three main species, a potentially important yet under-researched component of the global biosphere, carbon and water cycles. This review synthesises current knowledge on glacier algae phylogenetics, physiology and ecology. We discuss their significance for the evolution of early land plants and highlight their impacts on the physical and chemical supraglacial environment including their role as drivers of positive feedbacks to climate warming, thereby demonstrating their influence on Earth’s past and future. Four complementary research priorities are identified that will facilitate broad advances in glacier algae research, including: establishment of reliable culture collections, sequencing of glacier algae genomes, development of diagnostic biosignatures for remote sensing, and improved predictive modelling of glacier algae biological-albedo effects.